Detection of MagA Gene Among Clinical Isolates Of Klebsiella Pneumoniae Collected From Hospitals Of Qazvin, Iran - Alimohammadi, Laleh; Peymani, Amir; Habibollah-Pourzereshki, Narges (Malaysian Journal of Science, 2017)
Klebsiella pneumoniae is an opportunistic bacterium that causes serious hospital-acquired infections. Among the different virulence factors of the bacteria, capsule is the most important one and plays an important role in its mucoviscosity. The current cross-sectional study was conducted on 149 K. pneumoniae species isolated from different clinical samples obtained from patients hospitalized in teaching hospitals of Qazvin, Iran, from 2014 to 2015. All isolates were identified by laboratory standard methods. First, the isolates were evaluated for harboring the gene ureD, as an internal control, and the magA gene by polymerase chain reaction (PCR) and sequencing methods. All isolates were positive for the presence of ureD gene, the specific gene of K. pneumoniae. Eleven isolates (7.4%) harbored the magA gene which were mostly collected from trachea (4 isolates, 36.3%) and blood (3 isolates, 27.3%) specimens and from the patients admitted in intensive care units (9 isolates, 81.8%) and infectious diseases wards (2 isolates, 18.2%). Results of the current study showed the high prevalence of magA gene in K. pneumoniae isolated from hospitals in Qazvin city, Iran, which because of its engagement in capsule production, it is necessary to consider these organisms in prevention and treatment of the infection. Keywords: Klebsiella pneumoniae, polysaccharide capsule, magA